2013
DOI: 10.1021/ol402559z
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Holmium Complex-Catalyzed Diels–Alder Reaction of Silyloxyvinylindoles: Stereoselective Synthesis of Hydrocarbazoles

Abstract: The catalytic and asymmetric cycloaddition between 3-[1-(silyloxy)vinyl]indoles and electron-deficient olefins gave substituted hydrocarbazoles in up to 99% yield and 94% ee. This reaction was catalyzed by a novel chiral holmium(III) complex. Alkylation of the cycloadduct gave a tricyclic compound with four continuous chiral centers, one of which was a quaternary carbon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 48 publications
1
25
0
1
Order By: Relevance
“…Ever since, other chiral lanthanide catalysts have been applied to promote asymmetric Diels-Alder cycloadditions. As a recent example, Nishida et al reported asymmetric Diels-Alder cycloadditions of 3-[1-(silyloxy)vinyl]indole 51 with N-acyloxazolidinones 44a-k promoted by a novel chiral holmium catalyst in situ generated from Ho(NTf 2 ) 3 and chiral bis-thiourea ligand 52 [32]. The reaction was performed in dichloromethane in the presence of 10 mol% of DBU that was supposed to deprotonate the NH of the ligand.…”
Section: (Hetero)-dielsàalder Cycloadditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ever since, other chiral lanthanide catalysts have been applied to promote asymmetric Diels-Alder cycloadditions. As a recent example, Nishida et al reported asymmetric Diels-Alder cycloadditions of 3-[1-(silyloxy)vinyl]indole 51 with N-acyloxazolidinones 44a-k promoted by a novel chiral holmium catalyst in situ generated from Ho(NTf 2 ) 3 and chiral bis-thiourea ligand 52 [32]. The reaction was performed in dichloromethane in the presence of 10 mol% of DBU that was supposed to deprotonate the NH of the ligand.…”
Section: (Hetero)-dielsàalder Cycloadditionsmentioning
confidence: 99%
“…Holmium-catalyzed Diels-Alder cycloaddition of a 3-[1-(silyloxy)vinyl]indole with N-acyloxazolidinones, and synthesis of (À)-minovincine [32].…”
Section: Direct Aldol Reactionsmentioning
confidence: 99%
“…Yb(OTf) 3 (47.1 mg, 76.0 µmol) and (R)-BINUREA (6) 3) (44.1 mg, 76.0 µmol) taken in a test tube with a stirring bar were heated at 120°C under reduced pressure (<0.1 mmHg) for 30 min. After being allowed to cool to room temperature, the test tube was charged with dry argon.…”
Section: -((1r6s)-6-(4-methylpent-4-en-1-yl)-4-oxocyclohex-2-ene-1-mentioning
confidence: 99%
“…Both functionalized compounds could be potential synthetic intermediates, and we have previously demonstrated the synthetic utility of this reaction. [4][5][6][7] In the present study, silyloxy-substituted cyclohexadiene 7 derived from 4 was shown to be a key intermediate for two types of synthetically useful chiral building blocks, i.e., the tricyclo[4.3.1.0 3,7 ] decane (isotwistane 8, n=1) and tricyclo [5.3.1.0 3,8 ] undecane (homoisotwistane 8, n=2) skeletons via the intramolecular Diels-Alder reaction, and aminocyclitol 10 via the intermolecular hetero-Diels-Alder reaction with nitrosobenzene (Chart 2).…”
mentioning
confidence: 99%
“…The reported [4+2]-cycloaddition of silyloxyvinylindoles 4 provides an expedient stereoselective entry into hydrocarbazoles 7 (Scheme 2), as well as hydroindoles and hydrobenzofurans. 29 The obtained chiral cycloadducts could serve as potential synthetic intermediates for Strychnos alkaloids.…”
Section: Introductionmentioning
confidence: 99%